2019
DOI: 10.1016/j.euromechflu.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Angle of attack dependence of flow past cactus-inspired cylinders with a low number of ribs

Abstract: The aerodynamic coefficients and the Strouhal number of cylinders with three and four ribs, inspired by succulents Euphorbia trigona and Euphorbia Abyssinica are investigated using 2D Unsteady Reynolds-Averaged Navier-Stokes simulations at Reynolds number 20,000. Both configurations show a significant dependence of the studied characteristics on the angle of attack. The obtained results are compared to the smooth circular cylinder, previous results for cylinders with 24 ribs based on the Saguaro cactus, and cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Similar behaviour was previously observed in a URANS-based investigation of a cactus-shaped cylinder with four ribs (Zhdanov and Busse, 2019).…”
Section: Critical Angle Of Attacksupporting
confidence: 87%
See 1 more Smart Citation
“…Similar behaviour was previously observed in a URANS-based investigation of a cactus-shaped cylinder with four ribs (Zhdanov and Busse, 2019).…”
Section: Critical Angle Of Attacksupporting
confidence: 87%
“…Taking into account that these succulents have developed their plant features, including ribs, independently from cacti through the process of convergent evolution (McGhee, 2011), their shape may provide aerodynamic benefits similar to those of cactus-shaped cylinders with many ribs. In a 2D URANS study it was found that a succulent-inspired cylinder with four ribs has superior aerodynamic behaviour compared to the regular square cylinder at certain angles of attack (Zhdanov and Busse, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The studied shape is identical to the shape investigated in our earlier studies using 2D URANS (Zhdanov and Busse 2019) and experimental (Zhdanov et al 2021) approaches. The cross-section of the cylinder (Fig.…”
Section: Numerical and Experimental Setupsupporting
confidence: 57%
“…The variation of these quantities with angle of attack from the present large eddy simulations are shown in Figs. 3 and 4, where they are also compared to experimental (Zhdanov et al 2021) and 2D URANS (Zhdanov and Busse 2019) data for the same shape.…”
Section: Force Coefficients and Strouhal Numbermentioning
confidence: 99%
See 1 more Smart Citation